Bosnia and Herzegovina Railways Policy Note - World Bank (Washington, DC: World Bank, 2016)
This Policy Note has been prepared to assist the governments of the Entities in Bosnia and Herzegovina to better understand the current conditions of the railway sector,assess the policy options for modernizing it and help chart a course ahead. Railway performance is benchmarked against a number of regional comparator countries and against the European Union average. The financial performance of each railway has been examined by main business sectors (freight, passenger and network infrastructure) using a railway cost allocation model developed by the Bank. Sector policies have also been assessed in terms of budget impact. Public policy decisions on the railway sector are the prerogative of the governments ofthe Entities. To help inform their decisions a range of structural and policy options is presented, their key features delineated and relative merits discussed. The range of policy options has been discussed with representatives of the Entity governments and railways butno endorsement of any policy option has been given at this stage. The Policy Note does present the Bank team’s opinions on certain of the options where this seems warranted but is not intended to be prescriptive.